Automatic Speech Recognition For Voip With Packet Loss Concealment - Adil Bakri; Abderrahmane Amrouche; Mourad Abbas; Lallouani Bouchakour (Al-Lisaniyyat)
This paper proposes a packet loss concealment (PLC) technique for increase the robustness of automatic speech recognition (ASR) of speech coded with the G729 codec, on the Voice over Internet Protocol (VoIP). Many of the standard ITU-T CELP based speech coders, such as the G.723.1, G.728, and G.729, model speech reproduction in their decoders. These decoders have enough state information to integrate PLC algorithms directly in the decoder, and are specified as part of their standards in particular by PLC based ITU-T G711 Appendix I. Speech is transmitted with source and channel codes optimized, this channel is simulated by two states Markov model to modeled loss packets. The objective of PLC based ITU-T G711 Appendix I is to generate a synthetic speech signal to cover missing data or loss packets in a received bit stream for the ASR application, i.e., to minimize word error rate.